Making the Past Audible: The Childlike Element and Renewal of Existence in Benjamin and Woolf - Anne-Marie Smith-Di Biasio (Sillages Critiques)
This paper reads Virginia Woolf’s writing through Walter Benjamin’s thinking of “the childlike element” as a paradigm of renewal, whereby, through the prism of memory, the recall of a remainder sealed in the old world will reignite the promise of hope crystallized in childhood. For in Benjamin’s thinking, traces of the past, including residues of previous generations, demand from the future, in the figure of the child, their promise of redemption. In this context, against the background of Theses on the Philosophy of History, we read Berlin Childhood around 1900, written between 1932 and 1933, as a collection of fragments of memory brought together in search of the promise of redemption amidst the catastrophes of history. This analysis is extended to Virginia Woolf in terms of reading acoustic anteriority as a form of language renaissance in To the Lighthouse, whereby through a radical infra-lyrical turn, words are heard anew in their oldness at a dialectical moment of danger. This allegory of renaissance is also a foundational paradigm in “Anon.” The secret index by which the past is referred to its resurrection and transfigured is further explored in Berlin Childhood and related to Benjamin’s definition in The Theses of the ‘zero hour’ of Stillstellung, which we then read as a moment when listening is suspended and time dislocated in Woolf’s The Waves. Further exploring this Modernist turn, whereby renaissance is synonymous with the temporal dislocation of afterlife, we then read extracts from Benjamin’s Berlin Childhood and Woolf’s “A Sketch of the Past” in terms of a broken chôric moment at which, in a ‘secret protocol’ (Verabredung) with the generations of the past, childhood memory returns as the event of a remainder.